2012
DOI: 10.1002/chem.201202438
|View full text |Cite
|
Sign up to set email alerts
|

Aza‐BODIPY Derivatives: Enhanced Quantum Yields of Triplet Excited States and the Generation of Singlet Oxygen and their Role as Facile Sustainable Photooxygenation Catalysts

Abstract: A new series of aza-BODIPY derivatives (4 a-4 c, 5 a,c, and 6 b,c) were synthesized and their excited-state properties, such as their triplet excited state and the yield of singlet-oxygen generation, were tuned by substituting with heavy atoms, such as bromine and iodine. The effect of substitution has been studied in detail by varying the position of halogenation. The core-substituted dyes showed high yields of the triplet excited state and high efficiencies of singlet-oxygen generation when compared to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(138 citation statements)
references
References 91 publications
3
127
0
Order By: Relevance
“…Thus 5a can be used as triplet photosensitizer for photosensitizing of singlet oxygen ( 1 O 2 ). This theoretical prediction is in agreement with the experimental results [1,47].…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Thus 5a can be used as triplet photosensitizer for photosensitizing of singlet oxygen ( 1 O 2 ). This theoretical prediction is in agreement with the experimental results [1,47].…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…Figure 8p resents, for comparison, the structures, triplet state properties and singlet oxygen formation quantum yields of all halogenated aza-BODIPYs reportedu ntil 2017. [35,41,64,65] We demonstrated that the iodinated aza-BODIPYs 5-8,i n contrastt ot he non-iodinated counterparts 1-4,p roduce highly populated triplet state upon excitation, as evidenced by the observation of transient absorption spectra and lack of room-temperature emission from the singlet excited state (S 1 !S 0 ). In addition, iodinated aza-BODIPYs 5-8 efficiently harvest visible light, as evidenced by their relatively high molar absorption coefficients (e), viz.…”
Section: Discussionmentioning
confidence: 96%
“…54 Those bearing six heavy atoms were particularly effective. As presented in Scheme 23, one of them was tested for the photooxidation of 1-naphthol into 1,4-naphthoquinone under normal sunlight conditions using acetonitrile as the solvent and with a continuous stream of oxygen.…”
Section: Visible-light-bodipy-mediated Transformationsmentioning
confidence: 99%